Kannan-Type Contractions on New Extended b-Metric Spaces - Hassen Aydi; Muhammad Aslam; Dur-e-Shehwar Sagheer; Samina Batul; Rashid Ali; Eskandar Ameer (Journal of Function Spaces)
This article is focused on the generalization of some fixed point theorems with Kannan-type contractions in the setting of new extended b-metric spaces. An idea of asymptotic regularity has been incorporated to achieve the new results. As an application, the existence of a solution of the Fredholm-type integral equation is presented.